Can the Global Forest Sector Survive 11 °C Warming?. (27th September 2018) - Favero, Alice; Mendelsohn, Robert; Sohngen, Brent
Abstract : Although most global forest economic studies have found that warming is likely to increase forest supply, these studies have examined only the limited warming expected through 2100. This study extends the analysis out to 2250 to test much higher levels of warming to examine very long term effects. Future warming is predicted to steadily increase forest productivity, with global timber supply predicted to increase through 2250, even with warming up to 11 °C warming. However, natural forestland and biomass will shrink. This result suggests far future forests will not be able to hold the same stock of carbon they hold today.